Critical periode of weed control in Zea mays L. - wilter januardi padang; Edison Purba; Eva Sartini Bayu (Universitas Sumatera Utara, 2017)
Weeds are really making disadvantages on corn (Zea mays L.). Since they compete to obtain light, water and nutrient. The competition may occur in the beginning until the harvesting time. The aims of this research is to determinate the critical periode of weed control on corn (Zea mays L.). The present study was conducted at exfarming field of corn, Tanjung Sari, Medan selayang. Variable factor being observed were plant height, initiation time of flower, dry weight of grain per sample, dry weight of grains per plot, weight of 100 corn grains, value harvesting indeks, height of weeds, dry weight of weeds and density of weeds. There were 12 treatments conducted, no weeds 2 week after planting : P1, no weeds 4 week after planting : P2, no weeds 6 week after planting : P3, no weeds 8 week after planting : P4, no weeds 10 week after planting : P5, no weeds are found till the harvesting time : P6, weedy until 2 week after planting : P7, weedy until 4 week after planting : P8, weedy until 6 week after planting : P9, weedy until 8 week after planting : P10, weedy until 10 week after planting : P11, weedy until the harvesting time : P12. The treatment were arranged in a randomized block design with three replication. The result showed that the weeding time for corn has non significantly affected to the plant height, dry weight of grains per sample, value harvesting indeks and dry weight of grains per plot, but significantly affected to the weight of 100 grain of corn.The filed of research was dominated by Eleusine indica. The critical periode of corn was happened of 21 day after planting up to 28 days after planting. Key words: corn, critical periode, weed, weeding periode